Differential effects of electroacupuncture and manual acupuncture on spontaneously hypertensive rats: insights from intestinal microbiota and metabolomics - Liu, Ji-Peng; Tu, Long-Teng; Yang, Ke-Zhen; Li, Yin-Yin; Gong, Yu; Han, Bing-Xuan; Liu, Chuan; Xia, Tian-Qi; Liu, Yu; Hao, Xiao-Min; Yue, Bing-Nan; Zhang, Jing; et al. (Frontiers in Molecular Biosciences, 2025)
BackgroundHypertension is a significant risk factor for cardiovascular disease, and acupuncture has demonstrated therapeutic effects in managing hypertension. However, the precise antihypertensive mechanisms of acupuncture require further elucidation.MethodsIn this study, 30 male spontaneously hypertensive rats (SHRs) and 10 male Wistar Kyoto (WKY) rats were utilized as experimental models. The SHRs were randomly assigned to three groups: the model group (Group M), the electroacupuncture group (Group EA), and the manual acupuncture group (Group MA), while the WKY rats served as the blank control group. Treatment was given every other day for 8 weeks, and systolic and diastolic blood pressures were measured every 2 weeks during the intervention period. Upon completion of the intervention, analyses of intestinal flora, as well as serum and fecal metabolomics, were conducted.ResultsThe findings indicated that both EA and MA effectively reduced systolic and diastolic blood pressure in SHRs, with EA demonstrating a more rapid onset of blood pressure reduction. EA and MA influence the composition of intestinal microbiota in SHRs, aligning the microbial structure more closely with that of the WKY group. This modulation results in an increased abundance of beneficial bacteria, such as Blautia, and a decreased abundance of harmful bacteria, such as Helicobacter. Regarding serum metabolomics, EA and MA affect metabolic pathways involving glycerophospholipids, linoleic acid, and arachidonic acid. In terms of fecal metabolomics, both acupuncture techniques are implicated in primary bile acid biosynthesis, dopaminergic synapse function, and sphingolipid signaling pathways. Notably, EA exerts a more significant influence on the steroid hormone biosynthesis pathway, whereas MA impacts the tryptophan metabolic pathway.ConclusionBoth EA and MA demonstrate antihypertensive effects by modulating intestinal microbiota composition and metabolite profiles in SHRs, although the specific microbiota and metabolites affected differ between the two techniques, and EA treatment reversed more fecal and serum metabolites than did MA. This study serves as a reference for investigating the mechanisms underlying acupuncture in the treatment of hypertension and facilitates its clinical application.